Perspectives before incremental trans-disciplinary cross-validation of clinical self-evaluation tools and functional MRI in psychiatry: 10 years later - Stoyanov, Drozdstoy (Frontiers in Psychiatry, 2022)
Translational validity (or trans-disciplinary validity) is defined as one possible approach to achieve incremental validity combining simultaneous clinical state-dependent measures and functional MRI data acquisition. It is designed under the assumption that the simultaneous administration of the two methods may produce dataset with enhanced synchronization and concordance. Translational validation aims at “bridging” the explanatory gap by implementation of clinically validated psychometric tools in the experimental settings of fMRI and then translating them back to clinical utility. Our studies may have identified common diagnostic task specific denominators in terms of activations and network modulation. However those common denominators need further investigation to determine whether they signify disease or syndrome specific features (signatures), which in the end of the day raises one more time the question about the poverty of current conventional psychiatric classification criteria. We propose herewith a novel algorithm for translational validation based on our explorative findings. The algorithm itself includes pre-selection of a test based on its psychometric characteristics; adaptation to functional MRI paradigm, exploration of the underpinning whole brain neural correlates in healthy controls as compared to patient population with certain diagnosis and finally, investigation of the differences between two or more diagnostic classes.